Training on the Making of Eco-Enzyme Disinfectants as a Sustainable Strategy for Processing Organic Waste - Retno Agnestisia; Erwin Prasetya Toepak; Yuliana Yuliana; Rizki Rachmad Saputra; Marvin Horale Pasaribu; Abed Nego Purba; Okta Prianus (Universitas Lambung Mangkurat, 2024)
The community in Habaring Hurung Urban Village, Bukit Batu District, Palangka Raya City, is grappling with the issue of accumulating household waste, primarily composed of organic waste. The prevalent practices of managing this waste, such as landfilling, burning, or haphazardly piling it around residential areas and roadsides, pose environmental and health risks. In response to this challenge, an initiative was undertaken to empower families in Habaring Hurung Urban Village through training sessions on creating disinfectants using eco enzymes derived from fermented organic waste. The method of implementing community service consists of the preparation stage, namely digging up information on training needs, and preparing materials and teaching aids; the implementation stage in the form of pre-final tests and training; and the last stage in the form of evaluation and reporting, took place on September 4, 2023, at the office hall of Habaring Hurung Urban Village. A total of 39 participants actively engaged in the training, displaying enthusiasm and a positive response. The results of the questionnaire also showed a fairly good level of satisfaction of all participants regarding the theme of the activity, the presentation was easy to understand, the participants' knowledge increased, and this activity should be continued by all participants where the percentage of participants who agreed showed a value of 56.4%. 51.3%, 66.7%, and 53% respectively. The ultimate goal of this initiative is to educate the local community on transforming organic waste into multifunction products for everyday use.